The inefficient advantage of experience in the market for football managers - Thomas Peeters; Stefan Szymanski; Marko Terviö (Tinbergen Institute, 2017)
We study hiring in a labor market where worker ability can only be observed on-the-job, but quickly becomes public information after labor market entry. We show that firms in these markets have a socially inefficient incentive to hire low talented, experienced workers instead of more promising labor market entrants, either when an extremely poor hire may bankrupt the firm, or when workers cannot commit to long-term contracts. In a dataset covering 38 years of hiring in the English labor market for football managers, we find that in around one quarter of all cases, where a firm hires an experienced worker, this experienced worker has an estimated ability below the average ability of recent labor market entrants. We argue this hiring behavior is inefficient, because it has persistently depressed the average ability of the active manager labor force over our sample period.
Keywords: M51; J63; J24; Z22; 330; hiring; labor market entrants; worker ability; European football